APPLICATION OF MULTIMEDIA-BASED LEARNING MODELS USING WEB-BASED LEARNING METHODS TO SUPPORT STUDENT CENTERED LEARNING IN SMA NEGERI 4 BANDUNG - Firmansyah Firmansyah; Eris Dwi Purnama (Jurnal Ilmiah Sistem Informasi, 2022)
Learning, in practice is inevitable from the use of technology, especially Information Technology (IT). IT has been able to contribute to the world of education. Learning is increasingly effective, interactive, broad, and unpatterned just in the classroom. Web Based Learning is a distance learning application using the online internet. This method of learning with the application bridges conventional learning problems such as the limitations available to teachers and students in the classroom. The purpose of this study is to build web-based learning as an online learning medium for high schools (SMA). The research was carried out by observing the system directly so that the results of the analysis of the needs of the system to be made were obtained. Literature studies are also carried out to find other sources that can be the basis and reference in creating a web-based learning system. The web based learning system is created using the PHP programming language and MySQL database. It can be concluded that the web-based learning application has been designed and implemented with facilities including downloading materials, assignments, quizzes, and open discussion forums for teachers and students to discuss with each other